Unveiling the Power of Authenticity: How Can Influencer and Brand Authenticity Drive Gen Z’s Purchase Intention Through Customer Involvement in Indonesia - Fitriani, Lili Karmela; Nurhasanah, Ade; Rahmantya, Yanneri Elfa Kiswara (Department of Management, Faculty of Economics and Business, Brawijaya University, 2025)
Digital disruption in business has reshaped the way consumers access, process, and respond to information, and this shift has significantly changed shopping behavior, especially in the beauty industry, which depends on trends, visual presentation, and personal trust. TikTok has become a major interactive platform for Generation Z in Indonesia, where lifestyle interests, entertainment, and product references are explored and developed. Through TikTok Shop, purchasing activities are directly connected to consumed content, and influencers function as key actors who shape purchase intention. The growing use of promotional content with exaggerated claims in beauty marketing has increased consumer concern because misleading information and unrealistic expectations can cause financial and health-related risks and gradually reduce trust in beauty brands. This study analyzes the influence of influencer authenticity and brand authenticity on purchase intention with customer involvement as a moderating variable. Using a quantitative approach, data were collected from 600 individuals from Generation Z active TikTok user analyze using SEM PLS. The findings show that influencer authenticity and brand authenticity have a positive and significant effect on brand attitude and purchase intention, which highlights authenticity as an essential factor in building consumer trust and credibility.